Conflitos, anomalias e disparidades : a psicologia como recurso à gestão do cotidiano escolar - Dametto, Jarbas (2008)
This research treats of the relations between school institution and psychological know that shows as an attribute technological available for management of the conflicts results of the unadaptation and subjective heterogeneity, on encounter between student and school. For that exploration and understanding, realized a bibliographyc revision for to plot a historic about the psychic suffering on western society and for to arrive until an approximation between abnormally and school, which is the main issue of this work. For to check the link between psychology and school, on a present and approximate realitty, we realized a empirical research who were analysed the informations forms about the school s expectations according to work developmented by professionals who act on psychology and psychiatry area, sended by the Centro Municipal de Atendimento ao Educando of the Passo Fundo RS, requesting psychological assessment for students, during 2006. For the theoretical reference, were utilised the Michel Foucault (1926-1984) studies, who contemplate the dynamics of power and know into modern institutions, whose was produced speechs of truth and ways of subjectivity.It was noticed that the psychology is requested for to solve many troubles, such as: difficulty of to manipulate in classroom (indiscipline); work with students who run away by school method; help to check and to establish (un)normality; answer moral conflicts and socio-familiar troubles that intervenes on school routine. It was also observed that the school is reference by education needs and to acquire health relief and to take social services, we conclude that arrive to the psychology requestions who overtake their confines. Furthermore, it was noticed that the results by the informations forms of Centro is evidence of failure on the school management, also failure of the extra-education public management who involve health, public safety and employement politics